2016
DOI: 10.15171/hpp.2015.035
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure and Health Impairments of Formaldehyde on Employees of a Wood Industry

Abstract: Background: Occupational exposure to formaldehyde may decrease white blood cell counts and change blood concentration. In this study, the influences of occupational exposure to formaldehyde on the number of white blood cells and blood concentrations were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…In accordance with this study, Jafari et al (2015) conducted case-control study at North Wood Factory, northern Iran, and revealed that the prevalence of eye, nasal, and throat irritation symptoms among exposed workers was significantly higher than the prevalence of irritation symptoms in the control group (Jafari et al 2015).…”
Section: Discussionsupporting
confidence: 68%
“…In accordance with this study, Jafari et al (2015) conducted case-control study at North Wood Factory, northern Iran, and revealed that the prevalence of eye, nasal, and throat irritation symptoms among exposed workers was significantly higher than the prevalence of irritation symptoms in the control group (Jafari et al 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Work in the wood industry is associated with exposure to wood dust [411], and in the particleboard industry the workers might also be exposed to formaldehyde from glue resin [1214]. Exposure to wood dust may cause acute irritation of the skin, eyes and airways [15, 16] and may also be associated with chronic respiratory symptoms [1618].…”
Section: Introductionmentioning
confidence: 99%
“…We are not aware of any other published data on such worst-case measurements of formaldehyde in particleboard industries. Full-shift measurements of formaldehyde in wood processing industries ranged from 0.5 to 1.52 ppm in Iran 34) and from 0.02 to 2.2 ppm in Turkey 35) , while mean area concentration of formaldehyde varied from 0.03 mg/m 3 to 0.31 mg/m 3 in Finland 36) . In an American study, short term formaldehyde level varied from 0.28 to 3.48 ppm 5) , and a geometric mean of 0.06 ppm was recorded in New Zealand 37) .…”
Section: Environmental and Occupational Health Practicementioning
confidence: 99%